2017
DOI: 10.1242/bio.027987
|View full text |Cite
|
Sign up to set email alerts
|

PQN-75 is expressed in the pharyngeal gland cells of C aenorhabditiselegans and is dispensable for germline development

Abstract: In Caenorhabditis elegans, five pharyngeal gland cells reside in the terminal bulb of the pharynx and extend anterior processes to five contact points in the pharyngeal lumen. Pharyngeal gland cells secrete mucin-like proteins thought to facilitate digestion, hatching, molting and assembly of the surface coat of the cuticle, but supporting evidence has been sparse. Here we show pharyngeal gland cell expression of PQN-75, a unique protein containing an N-terminal signal peptide, nucleoporin (Nup)-like phenylala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, when resisting the hypoxic stress response, the relative expression of this protein is reduced, thus slowing the aging process ( Kaufman et al, 2017 ), which is similar to our findings, and suggests that p -HBA can slow down the aging process by resisting hypoxic stress. PQN-75 is expressed in pharyngeal gland cells of C. elegans , and studies have shown that it protects the organism from acute temperature changes and has a protective effect on the high-temperature-induced stress response ( Rochester et al, 2017 ). Thus, the up-regulation of PQN-75 expression after administration of p -HBA suggests that p -HBA helps to resist high-temperature stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, when resisting the hypoxic stress response, the relative expression of this protein is reduced, thus slowing the aging process ( Kaufman et al, 2017 ), which is similar to our findings, and suggests that p -HBA can slow down the aging process by resisting hypoxic stress. PQN-75 is expressed in pharyngeal gland cells of C. elegans , and studies have shown that it protects the organism from acute temperature changes and has a protective effect on the high-temperature-induced stress response ( Rochester et al, 2017 ). Thus, the up-regulation of PQN-75 expression after administration of p -HBA suggests that p -HBA helps to resist high-temperature stress injury.…”
Section: Discussionmentioning
confidence: 99%